Dissipation of wave energy by a hybrid artificial reef in a wave simulator: implications for coastal resilience and shoreline protection. (20th October 2020) - Ghiasian, Mohammad; Carrick, Jane; Rhode‐Barbarigos, Landolf; Haus, Brian; Baker, Andrew C.; Lirman, Diego
Abstract: Coastal cities are susceptible to the impacts of waves, flooding, storm surge, and sea‐level rise. In response to these threats, coastal jurisdictions have invested in engineered shoreline defenses such as breakwaters and sea walls that are costly to implement and maintain. Thus, there is an increasing recognition that nature‐based defenses provided by healthy ecosystems like coral reefs can be an effective and cost‐efficient alternative to mitigate the impacts of climatic hazards while simultaneously restoring ecosystem services. Unfortunately, coral reefs have experienced degradation worldwide, lowering their potential for wave‐energy dissipation. As coastal vulnerability increases with the loss of natural barriers, it is imperative to design and test novel resilience solutions. Our study quantifies the benefits of hybrid artificial reefs for wave mitigation in a wave‐tank simulator using periodic waves of three heights (0.10, 0.16, and 0.24 m) at two water levels (0.55 and 0.65 m) defined considering the Froude similarity with a prototype reef structure in South Florida. Experiments showed that an artificial trapezoidal reef model reduces wave height (> 35%) and wave energy (up to 63%) under realistic wave conditions. Moreover, adding coral skeletons of Acropora cervicornis to simulate reef restoration onto the model mitigates up to an additional 10% of wave height and 14% of wave energy through increased friction, supporting the use of hybrid approaches that integrate both gray and green infrastructure to enhance coastal resilience. Exploring wave‐tank simulations provides a better understanding of wave effects before implementing larger and more costly projects in the field.